Synthesis and biological evaluation of dithiocarbamate esters of parthenolide as potential anti-acute myelogenous leukaemia agents - Yahui Ding; Zhongjin Yang; Weizhi Ge; Beijia Kuang; Junqing Xu; Juan Yang; Yue Chen; Quan Zhang (Taylor & Francis Group, 2018)
A series of dithiocarbamate esters of parthenolide (PTL) was designed, synthesised, and evaluated for their anti- acute myelogenous leukaemia (AML) activities. The most promising compound 7l showed greatly improved potency against AML progenitor cell line KG1a with IC50 value of 0.7 μM, and the efficacy was 8.7-folds comparing to that of PTL (IC50 = 6.1 μM). Compound 7l induced apoptosis of total primary human AML cells and leukaemia stem cell (LSCs) of primary AML cells while sparing normal cells. Furthermore, 7l suppressed the colony formation of primary human leukaemia cells. Moreover, compound 12, the salt form of 7l, prolonged the lifespan of mice in two patient-derived xenograft models and had no observable toxicity. The preliminary molecular mechanism study revealed that 7l-mediated apoptosis is associated with mitogen-activated protein kinase signal pathway. On the basis of these investigations, we propose that 12 might be a promising drug candidate for ultimate discovery of anti-LSCs drug.